Efficacy of hemostatic powders in lower gastrointestinal bleeding: Clinical series and literature review. Issue 10 (October 2021) - Facciorusso, Antonio; Bertini, Marco; Bertoni, Michele; Tartaglia, Nicola; Pacilli, Mario; Pavone, Giovanna; Ambrosi, Antonio; Sacco, Rodolfo
Abstract: Background: There is limited evidence on the efficacy of hemostatic powders in the management of lower gastrointestinal bleeding. Aims: to revise our series of patients with lower gastrointestinal bleeding treated with hemostatic powders and to provide a pooled estimate of their efficacy based on the current literature. Methods: Sixty-five patients underwent topical endoscopic application of hemostatic powder between 2016 and 2020. The primary endpoint was treatment success, with 7- and 30-day rebleeding rate, adverse events and mortality as secondary outcomes. Literature review was based on computerized bibliographic search on the main databases through December 2020. Pooled effects were calculated using a random-effects model. Results: Overall, the powder was applied as monotherapy in 37 patients (56.9%), as combination therapy in 15 patients (23.4%), and as rescue therapy in 13 cases (19.9%). Hemostasis was achieved in 100% of patients. Rebleeding rate at 7- and 30-day was 7.7% and 9.2%, respectively. A total of 10 studies with 259 patients were included in the meta-analysis. Immediate hemostasis was achieved in 96.3% (93.4%-99.2%) patients, whereas pooled 7- and 30-day rebleeding rates were 9.6% (4.5%-14.6%) and 12.9% (7.2%-18.5%), respectively. Conclusion: Novel hemostatic powders represent a user-friendly and effective tool in the management of lower gastrointestinal bleeding.